PUBLIC POLICIES INSPIRED BY PUBLIC-PRIVATE PARTNERSHIPS TO TECHNOLOGICAL LEAPS GAIN (ADMPG Journal, 2025)
This study looked at the interaction between public policies and collectively-owned companies or Township Village Enterprises – TVEs to achieve technological advances and leaps as strategies for regional economic progress of the leapfrogging catch-up type. The study indicated the convergence of the themes researched as contributions to the integration of countries into the global value chain and the consequent transition to large market economies throught public-private partherships.